2018
DOI: 10.1080/23802359.2018.1521311
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome of Narcissus poeticus L. (Amaryllidaceae: Amaryllidoideae)

Abstract: The first complete chloroplast genome sequence for Narcissus is assembled and annotated in this study. The total length of the N. poeticus chloroplast genome is 160,099 bp and comprises the large single copy (LSC) spanning 86,445 bp, the small single copy (SSC) spanning 16,434 bp, and two inverted repeat regions each of 28,610 bp length. The truncated copy of ycf1 before the junction between IR B and SSC was 1277–2428 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Type A-and B-like plastomes have been published previously e.g. Allium (Huo et al, 2019) and Narcissus (Könyves et al, 2018) respectively, however the Type C plastome, with the largest IR expansion, represents a novel rearrangement in Amaryllidaceae that has not been reported previously.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Type A-and B-like plastomes have been published previously e.g. Allium (Huo et al, 2019) and Narcissus (Könyves et al, 2018) respectively, however the Type C plastome, with the largest IR expansion, represents a novel rearrangement in Amaryllidaceae that has not been reported previously.…”
Section: Discussionmentioning
confidence: 72%
“…Amaryllidoideae, the most diverse subfamily with c. 75 genera (Meerow, Gardner & Nakamura, 2020), has a complex evolutionary history including hybridisation (García et al, 2017;Marques et al, 2017;Meerow, Gardner & Nakamura, 2020) and morphological convergence (Meerow, 2010). Arising from our research in horticulturally important Amaryllidaceae genera (Könyves et al, 2018(Könyves et al, , 2019aDavid & Könyves, 2019) here we report the sequencing and assembly of five Amaryllidoideae species and compare our assemblies with available Amaryllidaceae plastomes from GenBank. We found that most Amaryllidoideae plastomes are of typical organisation, however Strumaria truncata has experienced substantial rearrangements and gene losses.…”
Section: Introductionmentioning
confidence: 99%
“…The plastome is thought to occur in either circular or linear forms (Bendich 2014 ) containing a number of genes responsible for photosynthesis and their own housekeeping functions, such as protein synthesis, as shown with the plastome map of the daffodil Narcissus poeticus in Supplementary Fig. S1 (Könyves et al 2018 ). With incredibly large numbers of chloroplasts within photosynthetic cells, this plastome offers a valuable resource for phylogenetic studies as shown by the sheer number of angiosperm plastome sequences now available in the NCBI GenBank.…”
Section: Introductionmentioning
confidence: 99%
“…The first plastome sequence was published in 1986 coming from Nicotiana tabacum (Shinozaki et al 1986 ). However, the first daffodil plastome was only published in 2018 (Könyves et al 2018 ). This complete plastome from Narcissus poeticus (accession MH706763) was completed using Illumina HiSeq 4000 at the Oxford Genomics Centre, showing that the total plastome sequence was 160,099 base pairs (bp) with two inverted repeat (IR) regions, each of 28,610 bp length.…”
Section: Introductionmentioning
confidence: 99%
“…The complete plastome of Narcissus poeticus L. (MH706763; Könyves et al. 2018 ) was used as the starting seed for the NovoPlasty assembly. The memory was limited to 6 Gb.…”
mentioning
confidence: 99%